Impacts of land use and land cover on sediment production in a tropical peri-urban water source area - Jovino, Estephania Silva; Angelini, Ronaldo; Bressiani, Danielle Almeida; Cunha, Karina Patrícia Vieira; Costa, Carlos Willmer (Sociedade & Natureza, 2022)
The change of natural landscapes by anthropic activities is the main reason for the erosion deepening. Thus, it is necessary to know the processes that determine the hydrological balance to avoid erosion in this context. Due to the complexity of a basin and the need of making predictions, the development of mathematical models is essential for decision making. Among the existing models, the Soil and Water Assessment Tool (SWAT) is one of the most utilized models worldwide. Thus, the present study aims to compare the land use between different periods and quantify the soil loss in a basin (Feijão River, in the Brazilian southeast), using the SWAT + model, as also to provide guidance to decision making by determining priority areas to improve water quality. The simulation was performed by dividing the basin into sub-basins and assigning multiple HRUs. The metrics used to analyze the model's efficiency indicate that the results were satisfactory, Nash-Sutcliffe (NSE) of 0.53 and 0.54 for calibration and validation of streamflow, respectively. The model represented in this study can help guide future planning for land use and occupation of the basin, enabling the forecast of different scenarios and their possible impacts on water production.